Investigating hidden sectors at future e+e− colliders through two-particle angular correlations - Musumeci Emanuela (EPJ Web of Conferences)
Exploring long-range angular correlations among emitted particles in high-energy collisions provides an opportunity to uncover physics beyond the Standard Model like Hidden Valley (HV) models. We focus on a hidden QCD-like sector, where the interplay between HV matter and QCD partonic cascades could enhance azimuthal correlations between final-state particles. Our investigation, performed at detector level, specifically targets the detectability of these phenomena at future e+e− colliders, yielding a cleaner experimental signature as compared to the Large Hadron Collider (LHC). Remarkably, the observation of ridge structures in the two-particle correlation function may suggest the existence of New physics.